THE INFLUENCE OF WORK COMPETENCY, WORKLOAD, AND REWARD SYSTEM ON EMPLOYEE PERFORMANCE AT THE ECONOMIC DIVISION OF THE REGIONAL SECRETARIAT IN BATAM CITY - Ansori, Sayid; Sudianto, Sudianto; Suyono, Suyono; Sabri, Sabri (Yayasan Education and Social Center, 2025)
The purpose of this study is to investigate the impact of Job Competence, Workload, and Reward System on Employee Performance in the Economic Division of the Regional Secretariat in Batam City. The context of this study stems from the phenomenon of suboptimal employee performance, characterised by delays in completing macroeconomic reports and work results that do not meet organisational goals. The main factors suspected of influencing this condition are employee competencies that do not fully match job demands, disproportionate distribution of workloads, and an ineffective and unfair reward system. This study uses a quantitative, associative research design. The study population consisted of 35 employees, all sampled using a saturated sampling technique. Data were collected using a Likert-scale questionnaire and analysed using multiple linear regression in SPSS version 25. The results of the study indicate that Job Competence, Workload, and Reward System have a positive and significant effect on Employee Performance, both partially and simultaneously. The coefficient of determination (R²) of 0.742 indicates that these three variables explain 74.2% of the variation in Employee Performance, while factors outside the research model explain the remaining 25.8%. This finding underscores the importance of enhancing competency, managing a balanced workload, and implementing a fair and transparent reward system to boost employee performance.